Serum levels and activity of indoleamine2, 3-dioxygenase and tryptophanyl-tRNA synthetase and their association with disease severity in patients with chronic kidney disease. (7th May 2013) - Bao, Yu-Shi; Ji, Ying; Zhao, Shi-Lei; Ma, Lin-Lin; Xie, Ru-Juan; Na, Shi-Ping
Abstract: Objective : This study aims to test the serum levels and activity of indoleamine2, 3-dioxygenase(IDO) and tryptophanyl-tRNA synthetase (TTS) in patients with chronic kidney disease (CKD) and to evaluate their association with disease severity. Method : Serum concentrations of IDO and TTS in 61 patients with CKD and 16 healthy volunteers were tested by ELISA. Tryptophan and kynurenine concentrations were measured by high-performance liquid chromatography (HPLC). Results : Patients with CKD showed higher serum levels of IDO and TTS in comparison to healthy controls ( p = 0.001). Patients with CKD showed lower serum levels of tryptophan and higher serum levels of kynurenine in comparison to healthy controls ( p < 0.001). The kyn/Trp ratio significantly correlated with the disease severity in CKD patients ( r = 0.721; p < 0.001). Conclusions : IDO and TTS may play critical roles in the immune pathogenesis of CKD. The activity of IDO correlated with the disease severity of CKD.